2016
DOI: 10.1097/pas.0000000000000536
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of Mixed Endometrial Carcinomas Shows Clonality in Most Cases

Abstract: Mixed endometrial carcinoma refers to a tumor that is comprised of two or more distinct histotypes. We studied 18 mixed-type endometrial carcinomas - 11 mixed serous and low-grade endometrioid carcinomas (SC/EC), 5 mixed clear cell and low-grade endometrioid carcinomas (CCC/EC), and 2 mixed clear cell and serous carcinoma (CCC/SC), using targeted next generation sequencing and immunohistochemistry to compare the molecular profiles of the different histotypes present in each case. In 16 of 18 cases there was mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 40 publications
2
34
0
Order By: Relevance
“…However, in our study we assigned those cases to either the endometrioid or the clear cell type, depending on the predominant morphology, assisted by IHC (see ). Similarly, we recently demonstrated that four of five ‘mixed’ endometrial clear cell–endometrioid carcinomas had dMMR . Regarding the question of which clear cell carcinomas may be selected for dMMR testing, we cannot present a reliable age cut‐off, but our patients were aged 48–55 years (perhaps <60 years).…”
Section: Discussionmentioning
confidence: 86%
“…However, in our study we assigned those cases to either the endometrioid or the clear cell type, depending on the predominant morphology, assisted by IHC (see ). Similarly, we recently demonstrated that four of five ‘mixed’ endometrial clear cell–endometrioid carcinomas had dMMR . Regarding the question of which clear cell carcinomas may be selected for dMMR testing, we cannot present a reliable age cut‐off, but our patients were aged 48–55 years (perhaps <60 years).…”
Section: Discussionmentioning
confidence: 86%
“…In a single case there was failure to sample a dedifferentiated component of a tumor in the biopsy, a rare EC variant associated with mutations in chromatin remodelling genes and frequent MMR protein [34, 35]. In theory, mixed carcinomas may also pose a challenge to classify using ProMiSE, however, truly biologically mixed tumors are exceptionally rare [36] and most cases diagnosed as mixed carcinoma are actually due to morphologic ambiguity rather than admixtures of molecularly distinct clones [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Fundamental features of the immunophenotype for dedifferentiated, clear cell, and mixed carcinomas have been reported [50, 54, 109111]. Assessment of mixed tumors show that despite morphologic differences/mimicry, the majority of molecular aberrations are shared across the tumor [112]. Thus the application of ProMisE or Leiden classification systems to these cancers may be of value.…”
Section: Rare Histotypes and Diversity Within Tumorsmentioning
confidence: 99%